Kritična presoja vloge gozdnih rezervatov in gospodarjenja z gozdovi v Sloveniji pri ohranjanju biotske raznovrstnosti - Grce, Dragomir (Gozdarski vestnik, 2014)
The paper evaluates the role of the forest reserve network in Slovenia for both research purposes and conservation of biodiversity. In particular, we quantified the quantity and quality of dead wood in 16 forest reserves in Slovenia as a general indicator of conservation value. The total volume (standing and lying trees) ranged from 21,4 to 239 m3/ha, with a mean of 116,4 m3/ha, which is markedly higher than in surroundings managed forests. In most of the reserves, large dead trees in advanced stages of decay were present, indicating the high quality of dead wood in reserves. Given that recent recomendations from the literature call for 30-50 m3/ha of dead wood in managed forest to maintain the majority of saproxylic species, coupled with the small area of forest reserves in Slovenia (<1 % of forest cover), we conclude that the reserves are the only suitable habitats for maintaining specialist saproxylic species that require high quality dead wood. These results also indicate that current %close-to nature% management may not be sufficient for conserving many saproxylic species. For this reason, we believe that extending the network of forest reserves, as well as an increase in dead wood in managed forests, is essential for conservation of native forest biodiversity.
Keywords: gozdni rezervati; ohranjanje habitatov; biodiversity; biotska raznovrstnost; forestry; gozdarstvo